2019
DOI: 10.1136/bmjresp-2019-000438
|View full text |Cite
|
Sign up to set email alerts
|

Early identification of severe community-acquired pneumonia: a retrospective observational study

Abstract: BackgroundCommunity-acquired pneumonia (CAP) is a leading cause of sepsis worldwide. Prompt identification of those at high risk of adverse outcomes improves survival by enabling early escalation of care. There are multiple severity assessment tools recommended for risk stratification; however, there is no consensus as to which tool should be used for those with CAP. We sought to assess whether pneumonia-specific, generic sepsis or early warning scores were most accurate at predicting adverse outcomes.MethodsW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 35 publications
0
22
1
Order By: Relevance
“…[25] Another research in which 1,545 cases were enrolled demonstrated that overall accuracy assessed by ROC was more superior for CURB65 than for qSOFA, a qSOFA ≥2 at admission identifi ed 40.3% of those who died within 30 days, and thus advised use of pneumonia-specific tools rather than generic sepsis or early warning scores. [15] Song et al [26] enrolled 443 CAP patients, and results indicated that qSOFA with lactate was a useful and practical tool for the early identifi cation of in-hospital mortality among CAP patients in ED.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[25] Another research in which 1,545 cases were enrolled demonstrated that overall accuracy assessed by ROC was more superior for CURB65 than for qSOFA, a qSOFA ≥2 at admission identifi ed 40.3% of those who died within 30 days, and thus advised use of pneumonia-specific tools rather than generic sepsis or early warning scores. [15] Song et al [26] enrolled 443 CAP patients, and results indicated that qSOFA with lactate was a useful and practical tool for the early identifi cation of in-hospital mortality among CAP patients in ED.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] Only a few studies have investigated the prediction value of NEWS for the adverse clinical outcome of CAP on admission to EDs. [11,12,15] In this study, we investigated the accuracy of NEWS compared with other commonly used severity scores (CURB65, PSI, SOFA, qSOFA, and MEDS) and admission lactate levels in predicting clinical outcomes (28-day mortality, ICU admission, and mechanical ventilation use) for septic patients with CAP in ED.…”
Section: Introductionmentioning
confidence: 99%
“…Although prior reports have stated that the qSOFA, CURB-65 and SIRS scoring systems are simple and efficient methods for evaluating CAP severity, the present study found them inefficacious as prognostic tools for HCAP-associated mortality. 6,11,13 Differentiating each score from other pneumonia mortality prognostic factors is difficult, because the clinical symptoms that are reflected in each score, including a respiratory rate >22 respirations/min (tachypnea), systolic blood pressure <100 mmHg, altered mental status, consciousness disturbances (Glasgow Coma Scale score <15), heart rate >90 b.p.m. (tachycardia) or <40 b.p.m.…”
Section: Place Of Deathmentioning
confidence: 99%
“…Further studies reported that qSOFA and CURB-65 scores are useful for evaluating CAP and HCAP severity. 13,14 Most prior studies, however, have examined CAP in a fragmented way by evaluating just a few variables and ignoring the importance of AP-associated factors, despite the high incidence of AP in older adults with CAP and hospital-acquired pneumonia. 3 Therefore, we sought to comprehensively investigate the utility of AP-related factors, nutritional status, immune status, medication, comorbidities, and qSOFA, CURB-65 and SIRS scores for predicting HCAP mortality in older adults.…”
Section: Introductionmentioning
confidence: 99%
“…CURB65 score system includes ve indicators: altered mentation, blood urea > 7.0mmol/l, respiratory rate ≥ 30/min, systolic blood pressure < 90mmHg or diastolic blood pressure ≤ 60mmHg, and age ≥ 65 years old. Each of the indicators counts for one point, and scores ≥ 2 are classi ed as moderate-severe pneumonia [10]. Biomarkers are also widely used to assess the severity of pneumonia,including procalcitonin (PCT), C-reactive protein (CRP), and proadrenomedullin (proADM) [11][12][13].…”
Section: Introductionmentioning
confidence: 99%